1987
DOI: 10.1038/bjc.1987.63
|View full text |Cite
|
Sign up to set email alerts
|

Squamous and adenocarcinoma of the uterine cervix: a comparison using routine data

Abstract: Summary We studied the clinical, demographic and survival characteristics of more than 5,000 women registered with either squamous or adenocarcinoma of the uterine cervix in South Thames Cancer Registry over the period 1968-81. There were similarities with respect to social class, smoking habit, oestrogen/oral contraceptive use and time trends in incidence but differences between the two cancers were found with respect to age distribution, parity, method of detection and survival. Some of the data are of limit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
18
1
2

Year Published

1988
1988
2003
2003

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(22 citation statements)
references
References 26 publications
1
18
1
2
Order By: Relevance
“…No association with parity for either adenocarcinoma or squamous cell carcinoma of the cervix was found in two cohort studies (Kvale et al, 1988;Bjorge and Kravdal, 1996). Case -case studies have generally found adenocarcinoma to be more strongly associated than squamous cell carcinoma with nulliparity (Tasker and Collins 1974;Korhonen, 1980;Milsom and Friberg 1983;Silcocks et al, 1987), but these studies are difficult to interpret as most of them lack adequate adjustment for potential confounding factors. Previous studies of cervical cancer have found age at first birth to be an independent risk factor for squamous cell , but not for adenocarcinoma (Kvale et al, 1988;Parazzini et al, 1988, Bjorge andKravdal, 1996;Ursin et al, 1996;Munoz et al, 2002;Altekruse et al, 2003).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…No association with parity for either adenocarcinoma or squamous cell carcinoma of the cervix was found in two cohort studies (Kvale et al, 1988;Bjorge and Kravdal, 1996). Case -case studies have generally found adenocarcinoma to be more strongly associated than squamous cell carcinoma with nulliparity (Tasker and Collins 1974;Korhonen, 1980;Milsom and Friberg 1983;Silcocks et al, 1987), but these studies are difficult to interpret as most of them lack adequate adjustment for potential confounding factors. Previous studies of cervical cancer have found age at first birth to be an independent risk factor for squamous cell , but not for adenocarcinoma (Kvale et al, 1988;Parazzini et al, 1988, Bjorge andKravdal, 1996;Ursin et al, 1996;Munoz et al, 2002;Altekruse et al, 2003).…”
Section: Discussionmentioning
confidence: 98%
“…This may reflect a cohort effect similar to that seen for squamous cell carcinomas and related to increased exposure to HPV infection in women born since 1960 (Madeleine et al, 2001;Sasieni and Adams, 2001), and the fact that cervical screening may be less effective in detecting adenocarcinomas than squamous cell carcinomas (Clarke and Anderson, 1979;Mitchell et al, 1995;Bergstrom et al, 1999). Their relative rarity has limited attempts to define risk factors for adenocarcinomas and adenosquamous carcinomas of the cervix (Silcocks et al, 1987;Parazzini and La Vecchia, 1990;Kjaer and Brinton, 1993), but several recent controlled studies with relatively large numbers (over 100) of adenocarcinoma cases have provided clearer evidence (Ursin et al, 1994(Ursin et al, , 1996Bjorge and Kravdal, 1996;Thomas and Ray, 1996;Lacey et al, 1999Lacey et al, , 2000Lacey et al, , 2001Madeleine et al, 2001;Munoz et al, 2002;Altekruse et al, 2003). Of these studies, four (one cohort study (Bjorge and Kravdal, 1996) and three multicentre case -control studies from WHO (WHO, 1993;Thomas and Ray, 1995), IARC and the USA (Lacey et al, 1999(Lacey et al, , 2000(Lacey et al, , 2001Altekruse et al, 2003)) have directly compared risk factors for adenocarcinoma and squamous cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…The reasons for this increase are poorly understood. While one case series has documented a higher prevalence of oral contraceptive use among women with adenocarcinoma (Dallengach-Hellweg, 1984), other studies have found no evidence of different oral contraceptive use between women with adenocarcinoma and women with squamous malignancy (Silcocks et al, 1987) on between women with adenocarcinoma and control women (Brinton et al, 1987;Parazzini et al, 1988).…”
mentioning
confidence: 99%
“…This rise has been related, in terms of aetiological hypothesis, to oral contraceptive use in young women' (Peters et al, 1986). Further, the age distribution has been suggested to differ in various histotypes of cervical carcinoma, adenocarcinoma appearing later in life than squamous cell cancer of the cervix uteri (Menczer et al, 1978;Silcocks et al, 1987).From these descriptive epidemiological observations, it has been suggested that adenocarcinoma may differ in pathogenetic mechanisms and that its aetiology should be investigated with reference to hormonal, rather than infectious, aspects.Nonetheless, only scanty evidence has been published, to our knowledge, on risk factors for cervical adenocarcinoma from analytical epidemiological studies (Brinton et al, 1987;Silcocks et al, 1987). To assess the epidemiological features of invasive adenocarcinoma of the cervix, we have therefore analysed data from a hospital-based case-control study of cervical neoplasms conducted in the greater Milan area, Northern Italy.…”
mentioning
confidence: 99%
“…This rise has been related, in terms of aetiological hypothesis, to oral contraceptive use in young women' (Peters et al, 1986). Further, the age distribution has been suggested to differ in various histotypes of cervical carcinoma, adenocarcinoma appearing later in life than squamous cell cancer of the cervix uteri (Menczer et al, 1978;Silcocks et al, 1987).…”
mentioning
confidence: 99%